2017
DOI: 10.1007/s11906-017-0723-4
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Effects of Probiotics

Abstract: Gut dysbiosis in hypertension is characterized by (i) the gut microbioma that is less diverse and less rich with an increased Firmicutes/Bacteroidetes ratio and (ii) a decrease in acetate- and butyrate-producing bacteria and an increase in lactate-producing bacterial populations. The meta-analysis of the human studies supports that supplementation with probiotics reduces blood pressure. The mechanism of this antihypertensive effect of probiotics and its protective effect on endothelial function has not been fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 109 publications
(59 citation statements)
references
References 60 publications
0
56
0
3
Order By: Relevance
“…Nevertheless, we also found that acetate prevented endothelial dysfunction induced by AngII in a GPR-independent manner, because it was unaffected by its antagonists. A reduced GPR-41 expression in aorta has been associated to reduced plasma butyrate levels and high BP in spontaneously hypertensive rats, as compared to Wistar-Kyoto rats (Robles-Vera et al, 2017;Kim et al, 2018). Interestingly, we found that AngII downregulated both GPR41 and GPR43 in endothelial cells.…”
Section: Discussionmentioning
confidence: 48%
“…Nevertheless, we also found that acetate prevented endothelial dysfunction induced by AngII in a GPR-independent manner, because it was unaffected by its antagonists. A reduced GPR-41 expression in aorta has been associated to reduced plasma butyrate levels and high BP in spontaneously hypertensive rats, as compared to Wistar-Kyoto rats (Robles-Vera et al, 2017;Kim et al, 2018). Interestingly, we found that AngII downregulated both GPR41 and GPR43 in endothelial cells.…”
Section: Discussionmentioning
confidence: 48%
“…Regarding antihypertensive drugs, no specific study has investigated the effect of drugs on the gut microbiota. In contrast, many studies have shown that probiotics may have antihypertensive effects [243].…”
Section: Cardiovascular-renal Crosstalk Cardiorenal Syndromes and Tmentioning
confidence: 96%
“…Probiotics can be selectively used to introduce and expand new types of microorganisms. Probiotics exert antihypertensive effects in human hypertensive patients and rat with genetic hypertension (genetic hypertensive rats) . In fact, chronic consumption of Lactobacillus strains not only reduced BP, but also inhibited organ target damage and improved endothelial dysfunction in spontaneously hypertensive rats (SHR) .…”
Section: Introductionmentioning
confidence: 99%